Proactive logistics risk management – a system dynamics modelling approach. (21st November 2008) - Kara, Sami; Kayis, Berman
The relationships among organisations, suppliers as well as customers have resulted in complex logistics networks and have led to an increased set of risks that need to be managed in multi-site, multi-partner projects. In this article, a framework is built which incorporates both scientific and industrial feedback gathered. A system dynamics approach is utilised which simulates several risks identified in supply chain networks to establish inter and intra-relationships between various risk factors in the entire enhanced network of engineering projects. The environmental, organisational and supply chain networks related issues are considered by developing several influence diagrams for proactive logistics management.